BAKU-TBLİSİ-CEYHAN OİL PİPELİNE: IMPACT ON ENERGY SECURİTY - Khalilov Elmar Shirinbala (Theoretical Hypotheses and Empirical Results, 2025)
The "Baku-Tbilisi-Ceyhan (BTC) Oil Pipeline: Impact on Energy Security" focuses on the geopolitical and economic significance of the BTC pipeline, which connects Azerbaijan's oil fields to the Turkish Mediterranean port of Ceyhan. This pipeline, which started operation in 2006, is a critical energy infrastructure project that enhances energy security for both Azerbaijan and its international partners by diversifying oil transportation routes, reducing dependence on Russian and Iranian routes, and promoting regional stability. The BTC pipeline strengthens energy security by offering an alternative to traditional transit routes, minimizing the risks associated with potential disruptions, such as political instability or conflicts. Additionally, it has economic implications, fostering energy cooperation between countries in the region and contributing to the global oil supply. Furthermore, the BTC pipeline plays a key role in the diversification of energy supply for Europe and other markets, mitigating energy security risks related to supply concentration in specific regions. This makes the BTC pipeline an essential element in shaping the energy dynamics of the region and beyond.